1997
DOI: 10.1074/jbc.272.37.23111
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the Caspase-3/CPP32 Protease Cascade for Apoptotic Death following Cytokine Deprivation in Hematopoietic Cells

Abstract: Hematopoietic cytokines transduce cell survival signals, which are distinct from the signals necessary for the stimulation of DNA synthesis. Recently, the Ras and phosphatidylinositol 3-kinase pathways have been shown to play important roles in preventing apoptosis in various cell types, e.g. hematopoietic cells and neuronal cells. Withdrawal of cytokine(s), in turn, results in rapid inactivation of these survival pathways and eventually leads to cell death accompanied by the hallmarks of apoptosis. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

1998
1998
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 38 publications
3
54
0
1
Order By: Relevance
“…The fact that several disparate inducers of apoptosis, which probably act by di erent mechanisms (Boix et al, 1998), all lead to the loss of eIF4G indicates that the pathways activated by these agents converge on this target protein. Low serum conditions activate apoptosis in immortalized or transformed cell lines (Kulkarni and McCulloch, 1994;Wang and Pandey, 1995;Kawanishi, 1997), probably by depriving the cells of growth factors necessary to promote cell cycle progression (Ohta et al, 1997); cycloheximide is also an e cient inducer of apoptosis in a variety of cell types, perhaps because it blocks the synthesis of one or more proteins essential for the prevention of apoptosis (Martin et al, 1990;Collins et al, 1991;Ledda-Columbano et al, 1992;Ishii et al, 1997); the CD95 (Fas) receptor acts by binding a number of proteins to the`death domain' located on its intracellular portion; etoposide interacts with DNA topoisomerase II and induces DNA strand breaks. The point of convergence of these pathways at the level of eIF4G is most likely the activation of one or more`executioner' caspases (Longthorne and Williams, 1997; Kamada et al, 1997;Cohen, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that several disparate inducers of apoptosis, which probably act by di erent mechanisms (Boix et al, 1998), all lead to the loss of eIF4G indicates that the pathways activated by these agents converge on this target protein. Low serum conditions activate apoptosis in immortalized or transformed cell lines (Kulkarni and McCulloch, 1994;Wang and Pandey, 1995;Kawanishi, 1997), probably by depriving the cells of growth factors necessary to promote cell cycle progression (Ohta et al, 1997); cycloheximide is also an e cient inducer of apoptosis in a variety of cell types, perhaps because it blocks the synthesis of one or more proteins essential for the prevention of apoptosis (Martin et al, 1990;Collins et al, 1991;Ledda-Columbano et al, 1992;Ishii et al, 1997); the CD95 (Fas) receptor acts by binding a number of proteins to the`death domain' located on its intracellular portion; etoposide interacts with DNA topoisomerase II and induces DNA strand breaks. The point of convergence of these pathways at the level of eIF4G is most likely the activation of one or more`executioner' caspases (Longthorne and Williams, 1997; Kamada et al, 1997;Cohen, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is characterized by a series of cellular changes that lead ultimately to cell death (Hale et al, 1996;Rowan and Fisher, 1997;Nagata, 1997;Salvesen and Dixit, 1997). An essential aspect of these events is the sequential activation of a number of proteases with limited substrate speci®cities, the caspases (Fearnhead et al, 1995;Tewari et al, 1995;Enari et al, 1996;Salvesen and Dixit, 1997;Cohen, 1997;Longthorne and Williams, 1997;Ohta et al, 1997). Intensive research in recent years has investigated the properties of these enzymes, the nature of some of their substrates, and their relative relationships in the protease cascades required for execution of the apoptotic programme.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-independent cell death has now been described in several models of apoptosis including glucocorticoid induced thymocyte cell death, 30 growth factor withdrawal in haematopoietic cell death, 32 etoptoside, 31 44,48 were retained. These studies have demonstrated that, at least in these models, several apoptotic events are not regulated by the caspases, and that while caspase activity may be sufficient for apoptotic cell death, it is not always necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Given that this is true also in BaF3 cells, it is likely that Racmediated survival signals culminate in phosphorylation of BAD and thus induce anti-apoptotic actions of Bcl-X L . Moreover, a critical role of caspase 3, which serves as an essential e ector of apoptosis induced by various extracellular death signals, including Fas or tumornecrosis factor (TNF) stimulation, in death of hematopoietic cells upon IL-2 or IL-3 deprivation was recently reported (Ohta et al, 1997). Hence, it may be interesting to reveal the function of caspases in Ras or Rac-dependent cell survival.…”
Section: Phosphorylation Of Threonine-308 and Serine-473 Is Critical mentioning
confidence: 99%